Renewable energy sources as a new research area in tourism - NAWROT, Łukasz (Economics and Business Review, 2025)
The article identifies and describes a research gap in the tourism economy with regard to renewable energy sources and delineates the biggest research needs and challenges. First of all, the subject of the paper is the tourism phenomenon as a multidimensional research area. Then, the paper concentrates on the renewable energy sources (RES) market in the modern economy with particular regard to investment processes. It characterises investments and innovations in the tourism economy and presents the greatest research difficulties in this respect. The last part of the paper concerns the characteristics of a research gap in the tourism economy identified from where investments and innovations in RES meet. The summary includes effects and desired research directions related to the discussed phenomena.